A Relational Approach to Interprocedural Shape Analysis - Jeannet, Bertrand; Loginov, Alexey; Reps, Thomas; Sagiv, Mooly (University of Wisconsin-Madison Department of Computer Sciences, 2004)
This paper addresses the verification of properties of imperative programs with recursive procedure calls, heap-allocated storage, and destructive updating of pointer-valued fields-i.e., interprocedural shape analysis. It presents a way to apply some previously known approaches to interprocedural dataflow analysis-which in past work have been applied only to a much less rich setting-so that they can be applied to programs that use heap-allocated storage and perform destructive updating.